2019
DOI: 10.3390/app9030413
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tracking of MgO/Epoxy Nanocomposites: Effect of Surface Hydrophobicity

Abstract: Surface tracking has been one of the challenges for outdoor organic insulations, in electronic and electrical devices. In this paper, surface tracking behavior of nano-MgO/epoxy composite samples were measured according to the standard IEC 60112. Improved tracking resistance was obtained in nanocomposites with an 18.75% uplift in the comparative tracking index, and a decrease of 58.20% in the surface ablation area at a fixed 425 V. It was observed that the tracking resistance and surface hydrophobicity shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In fact, the effect of nano-sized fillers on the surface charge transport dynamics has also been demonstrated in previous studies on surface resistivity [7] and flashover voltage [29] of polymeric nanocomposites. In [7], an increase of surface resistivity with higher filler loadings was found for MgO/epoxy nanocomposites. A similar trend in the increase of surface resistivity was also reported in [7].…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In fact, the effect of nano-sized fillers on the surface charge transport dynamics has also been demonstrated in previous studies on surface resistivity [7] and flashover voltage [29] of polymeric nanocomposites. In [7], an increase of surface resistivity with higher filler loadings was found for MgO/epoxy nanocomposites. A similar trend in the increase of surface resistivity was also reported in [7].…”
Section: Discussionsupporting
confidence: 58%
“…This hydrophobic nature contributes to improved tracking resistance performance by preventing the surface from being wet by contamination. For example, it has been shown that degradation of tracking resistance is related to the decrease in the SCA for MgO/epoxy nanocomposites [7]. The results of Figure 6 also demonstrate that the difference in the SCA caused by different filler loading seems to be negligible for the considered micro-sized SiO2 and nano-sized ATH fillers.…”
Section: Surface Contact Anglementioning
confidence: 80%
See 3 more Smart Citations